Elucidating the Electrocatalytic CO2 Reduction Reaction over a Model Single‐Atom Nickel Catalyst. Issue 2 (10th December 2019) - Liu, Song; Yang, Hong Bin; Hung, Sung‐Fu; Ding, Jie; Cai, Weizheng; Liu, Linghui; Gao, Jiajian; Li, Xuning; Ren, Xinyi; Kuang, Zhichong; Huang, Yanqiang; Zhang, Tao; et al.
Abstract: Designing effective electrocatalysts for the carbon dioxide reduction reaction (CO2 RR) is an appealing approach to tackling the challenges posed by rising CO2 levels and realizing a closed carbon cycle. However, fundamental understanding of the complicated CO2 RR mechanism in CO2 electrocatalysis is still lacking because model systems are limited. We have designed a model nickel single‐atom catalyst (Ni SAC) with a uniform structure and well‐defined Ni‐N4 moiety on a conductive carbon support with which to explore the electrochemical CO2 RR. Operando X‐ray absorption near‐edge structure spectroscopy, Raman spectroscopy, and near‐ambient X‐ray photoelectron spectroscopy, revealed that Ni + in the Ni SAC was highly active for CO2 activation, and functioned as an authentic catalytically active site for the CO2 RR. Furthermore, through combination with a kinetics study, the rate‐determining step of the CO2 RR was determined to be *CO2 − +H + →*COOH. This study tackles the four challenges faced by the CO2 RR; namely, activity, selectivity, stability, and dynamics. Abstract : Ni‐che reaction : In situ reduction of nickel(II) 2, 9, 16, 23‐tetra(amino)phthalocyanine, anchored on the surface of carbon nanotubes, yields nickel single atoms. Advanced spectroscopy of the single‐atom catalyst reveals that Ni + is a highly active catalytic site for CO2 activation and reduction.